(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Nitrogen is basic and necessary element contributing to plant growth and development. It is one of the most nutritious fertilizers used in agriculture. Adding a sufficient amount of Nitrogen will increase production, but the excessive use of nitrogen fertilizers has led to environmental pollution and the deterioration of the ecosystem. The plants use 50% of the added nitrogen and the remaining portion is lost to the environment in various ways, and thus it will affect the farms and pollute the soil, air, and water. Consequently, it has negative effects on humans and animals, as the emission of NH3, N2O, and NO in gaseous form through denitrification and volatilization, which causes dangerous environmental problems, as well as an increase in the value of production due to the loss of fertilizers from the ecosystem. Therefore, nitrogen use efficiency (NUE) must be developed and enhanced through agricultural management to improve plant production. This review describes several factors that participate in the loss of nitrogen from soil-plant systems, such as nitrification, volatilization, filtration, denitrification, ammonium fixation, surface runoff, and stabilization, plant factors, temperature, rainfall and irrigation, tillage, soil texture, Crop residues and soil quality, nitrogen management